Industrial survival via management technology - Merrifield, D.Bruce (Journal of Business Venturing, 1988)
Advancing technology has become a primary driving force for allworld economies, and effective management of this function increasingly will determine the rise and fall of nations as well as of industries and individual businesses. Management, by definition, now has become the management of technology driven change, marked by the progressive collapse of product and process life cycles, previously measured in decades, but now more often in two to five year periods. However, effective deployment of limited technical resources must be based on a disciplined set of business decisions, made in response to well defined market opportunities that in turn have been integrated into a comprehensive business strategy. Powerful methodologies are available both to predict and quantify cost performance requirements needed for commercial success in the hyper competitive global marketplace. Unfortunately, a void has existed in academic curricula for engineers, scientists and business school students to meet this urgent need.